Landslides: A Guide to Researching Landslide Phenomena and Processes - Gaurina-Medjimurec, Nediljka (Handbook of Research on Advancements in Environmental Engineering, 2014)
The protection of clean water, air, and land for the habitation of humans and other organisms has become a pressing concern amid the intensification of industrial activities and the rapidly growing world population. The integration of environmental science with engineering principles has been introduced as a means of long-term sustainable development. The Handbook of Research on Advancements in Environmental Engineering creates awareness of the role engineering plays in protecting and improving the natural environment. Providing the latest empirical research findings, this book is an essential reference source for executives, educators, and other experts who seek to improve their project’s environmental costs.